GENERIC FRAMEWORK FOR VALVE STICTION DETECTION AND COMPENSATION WITH ANFIS-ACTIVATED DUAL-MODE MPC - JEREMIAH, SEAN SURAJ (2020)
Due to continuous motion, control valve performance tends to deteriorate over time due to the presence of static-friction, or widely known as, stiction. As stiction affects 20 to 30% of control valves, it can lead to high variability in product quality and an increased frequency of valve maintenance. Existing Model Predictive Control(MPC) based stiction compensation methods can remove oscillation.